2015
DOI: 10.1523/jneurosci.1585-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Signaling of Neuregulin-2 Mediates Formation of GABAergic Synapses and Maturation of Glutamatergic Synapses in Newborn Granule Cells of Postnatal Hippocampus

Abstract: Expression of neuregulin-2 (NRG2) is intense in a few regions of the adult brain where neurogenesis persists; however, little is understood about its role in developments of newborn neurons.To study the role of NRG2 in synaptogenesis at different developmental stages, newborn granule cells in rat hippocampal slice cultures were labeled with retrovirus encoding tetracycline-inducible microRNA targeting NRG2 and treated with doxycycline (Dox) at the fourth or seventh postinfection day (dpi). The developmental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
3
15
0
1
Order By: Relevance
“…Recent studies have also indicated that Nrg3 plays important roles in cortical development (Bartolini et al, ) and glutamatergic neurotransmission (Wang et al, ). Along with studies on Nrg2 as a regulator of dopaminergic and glutamatergic function (Lee et al, ; Vullhorst et al, ; Yan et al, ), the current evidence supports the concept that Nrgs 1, 2, and 3 perform distinct functions in the central nervous system (CNS). In order to gain an improved understanding of the roles played by these factors in the nervous system, it is essential to characterize their developmental expression patterns.…”
Section: Introductionsupporting
confidence: 84%
“…Recent studies have also indicated that Nrg3 plays important roles in cortical development (Bartolini et al, ) and glutamatergic neurotransmission (Wang et al, ). Along with studies on Nrg2 as a regulator of dopaminergic and glutamatergic function (Lee et al, ; Vullhorst et al, ; Yan et al, ), the current evidence supports the concept that Nrgs 1, 2, and 3 perform distinct functions in the central nervous system (CNS). In order to gain an improved understanding of the roles played by these factors in the nervous system, it is essential to characterize their developmental expression patterns.…”
Section: Introductionsupporting
confidence: 84%
“…The NSD-S and disruptive sets of variants (Table 1, Ten other genes that harboured prioritized variants, have been implicated in neuropsychiatric syndromes. We identified a variant (rs148371256) in NRG2 gene (Neuregulin 2) which was earlier reported to be associated with gamma band oscillations in schizophrenia with suggestive genome wide significance ( Konte et al, 2017 ) and the encoded protein neuregulin-2 has been shown to be critical for the formation and maturation of GABAergic synapses ( Lee et al, 2015 ) and its ablation results in dopamine dysregulation ( Yan et al, 2017 ). Another novel variant We also noted a variant (rs534059912) in GOLM1 gene (Golgi membrane protein 1), which was earlier reported in sporadic Alzheimer's dementia (AD) to influence the pre-frontal cortical volume ( Inkster et al, 2012 ).…”
Section: Rare Deleterious Variants In Mendelian Genes Segregate Withimentioning
confidence: 99%
“…Supporting this interaction are the findings that both NRG3 and ErbB4 mutant mice have increased gamma oscillations (Del Pino et al, ; Muller et al, ). NRG2 is thought to accumulate postsynaptically on the proximal dendrites of ErbB4 expressing dendrites of PV interneurons to act in an autocrine manner (Lee et al, ; Vullhorst et al, , ). As NRGs have multiple sources and express as membrane‐bound versus cleaved extracellular pools, it is of interest to determine how these different sources regulate visual plasticity.…”
Section: Introductionmentioning
confidence: 99%